An investigation into the impact of age and task type on oral interactions of young learners of Chinese as a second language - Yan, Jing (Studies in Second Language Learning and Teaching, 2026)
Oral interaction is crucial for second language learning because it provides opportunities to practice the target language and enhance the comprehensibility of both input and output (Long, 1981; Oliver, 2002; Swain, 2005). However, there is a paucity of research that has examined oral interactions among young learners of Chinese as a second language. This study involved 110 students aged 10-12 from five primary schools in Hong Kong. The study analyzed interaction patterns and topic management skills when they performed two types of tasks. Results showed that the most frequently displayed pattern was collaborative, followed by dominant/passive. Regarding the impact of task type, the percentages of collaborative and expert/novice patterns were higher in the required information exchange tasks than in the optional information exchange tasks. In addition, the required information exchange tasks triggered significantly more turns, target language, short-other-extensions, and other-extensions than the optional information exchange tasks. There was an increase in the exhibition of collaborative patterns and a decrease in dominant/passive patterns from Grades 4 to 6. However, there were no significant differences in the measures of topic management skills across the three grades.